Curcumin loaded Solid lipid nanoparticles enhanced efficacy in vascular dementia against Homocysteine induced toxicity - Bhagyasree Prathipati; Rohini P (International Journal of Phytomedicine, 2021)
Vascular dementia (VaD), a diverse group of brain disorders with cognitive decline is attributable to cerebrovascular pathologies. Recent studies have shown that mitochondrial dysfunctions and oxidative stress are involved in cognitive decline. The aim of the present study was designed to evaluate the effects of Curcumin loaded solid lipid nanoparticles (Cur-SLNP) in vascular dementia (VaD) against homocystiene (HCY) induced toxicity by behavioral and biochemical assessment in different regions of the brain. The sign of VaD i.e., learning and memory levels were evaluated with different behavioural assessment like plus maze test. Neurobehavioral analyses revealed that Cur-SLNP administration successfully ameliorated cognitive decline observed in HCY rats. Compared to HCY administration, Cur-SLNP 10 mg/kg and 25 mg/kg administration showed ameliorative effect in behavioural and biochemical assessment induced by HCY. We found that lipid peroxidation levels decreased significantly in striatum (p<0.01), cortex (p<0.001), and hippocampus (p<0.001) after oral administration of Cur-SLNP with HCY animals. Hence, the present findings suggest that the neuroprotective role of Cur-SLNP against HCY induced toxicity could be a novel and promising therapeutic strategy in VaD as well in other age-related neurodegenerative disorders.